Perancangan Media Promosi Melalui Instagram Produk New Normal Series Untuk Safana Vintage - Safitri, Shafa Devina; Nugraini, Siti Hadiati (CITRAKARA, 2025)
People are increasingly using social media as a means of promotion, especially since the Covid-19 pandemic when everything has started to go digital. Safana Vintage is a business that is increasingly promoted on social media but often does not generate an increase in sales. This design was carried out to create an interesting and communicative promotional media for Safana Vintage's new products, to prospective buyers, to increase sales of its new products. The method used in this design is a qualitative method through interviews, observation, literature study, and documentation. The data is then processed using the SWOT method to produce promotional strategies through online media on Instagram and Shopee. Other media used in promoting Safana Vintage's new products are brochures and y-banners fordirect promotional activities.